2006
DOI: 10.1103/physrevb.73.155334
|View full text |Cite
|
Sign up to set email alerts
|

High-field magnetoexcitons in unstrainedGaAsAlxGa1xAsquantum dots

Abstract: The magnetic field dependence of the excitonic states in unstrained GaAs/ Al x Ga 1−x As quantum dots is investigated theoretically and experimentally. The diamagnetic shift for the ground and the excited states are studied in magnetic fields of varying orientation. In the theoretical study, calculations are performed within the single band effective mass approximation, including band nonparabolicity, the full experimental threedimensional dot shape and the electron-hole Coulomb interaction. These calculations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 27 publications
3
25
0
Order By: Relevance
“…Thus, we are not considering tunneling of states, which have a lower energy than the conduction-band edge of the ''barrier'' material, as in vertically coupled dots, but tunneling at energies that are lower energy than those of isolated WL states, but still lie well above the conduction-band edge. A third and crucial difference is that here we are not discussing the coupling of the ground state, but of the excited states, whose lateral extent is typically between 1.5 and 2 times that of the ground state, 20,30 and was recently calculated to be about 66% more extended in isolated InAs/ InP QDs grown on a ͑311͒B substrate. 31 We can also compare the wave-function penetration in the two cases.…”
Section: B Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we are not considering tunneling of states, which have a lower energy than the conduction-band edge of the ''barrier'' material, as in vertically coupled dots, but tunneling at energies that are lower energy than those of isolated WL states, but still lie well above the conduction-band edge. A third and crucial difference is that here we are not discussing the coupling of the ground state, but of the excited states, whose lateral extent is typically between 1.5 and 2 times that of the ground state, 20,30 and was recently calculated to be about 66% more extended in isolated InAs/ InP QDs grown on a ͑311͒B substrate. 31 We can also compare the wave-function penetration in the two cases.…”
Section: B Discussionmentioning
confidence: 99%
“…Indeed, recent calculations have shown that, at least in the GaAs/ Al x Ga 1−x As system, the influence of different dot charge states on the shift of ground or excited state PL with magnetic field is negligible. 20 The corresponding exciton Bohr diameters are thus equal to 13 nm for the low QDD sample, and 15 nm for the high QDD sample. Assuming the low QDD sample as a reference, we can define the standard confinement coefficient in our QD as ⌫ 0 = D X0 / D D0 , where D X0 and D D0 are the exciton Bohr diameter and the measured AFM diameter, respectively, of QDs on the low QDD sample.…”
Section: A Magnetophotoluminescencementioning
confidence: 99%
“…where m * ↓e and m * e are perpendicular and parallel effective masses of the electron and m * e is the bulk electron effective mass of the material, α = 0.64 eV −1 and β = 0.70 eV −1 are the nonparabolicity parameters [18]. The Schrödinger equation is solved variationally by finding H min and the binding energy of the donor in a quantum well is given by the difference between the energy with and without Coulomb interaction.…”
Section: Theory and Modelmentioning
confidence: 99%
“…In the next section we present our results for the binding energy and photoionization cross section in GaAs-Ga 0.7 Al 0.3 As QDs. The structure dimensions (radius and length) and the values of the external parameters (hydrostatic pressure and electric and magnetic fields) have been chosen in accordance with available experimental works [18][19][20][21][22][23].…”
Section: Theoretical Frameworkmentioning
confidence: 99%